THE EFFECT OF USING KAHOOT! FOR TEACHING ENGLISH - Uralova, Hilola (Журнал иностранных языков и лингвистики, 2021)
Kahoot! Is the most popular game-based learning platform among language teachers. The present paper is one of the studies which is dedicated learning the effects of the Kahoot! for learning English. The article presents the results of the using Kahoot for learning, and more specifically, on how Kahoot! affects learners, performance, engagement and motivation.